Bad Debt Influence On The Sustainability Of The Economy Of The Country - Grigonyte, Ingrida (European Scientific Journal, ESJ, 2016)
The objective of this paper is to evaluate the impact of late commercial payments in business, measured by the EPI index, on the main socio-economic development indicators. Data sources include Eurostat data and annual reports of Intrum Justitia OY. The data used in the research refers to Lithuania. The method of stepwise regression analysis was chosen to test the hypothesized relationship because its parameters have a clear economic interpretation. The study found unfavourable influence of late commercial payments in business on certain socio-economic indicators of the country. This leads to the conclusion that a certain amount of late commercial debts in business can have a significant influence on the economic sustainability of the country. It is necessary to make a deeper/wider research to estimate the influence of late commercial payments on different economic and social indicators as well as measure the magnitude of the influence more precisely. In the absence of similar scientific research, this study provides an insight into the problematic situation of businesses and the influence of this situation on the economic sustainability of the country.